Pengaruh Sudut Sdu Turbinu Crossflow Terhadap Daya Dan Efisien Pada Pembangkit C - ZukronAlviandyRahmadhan; IndriRahamyuni; FazrolRozi; Ikhsan Yusda Prima Putra (ABEC Indonesia, 2022)
By requiring students to find solutions to problems that occur in society in different ways from one another, even with the same problem cases. With the same case but different solutions, students look for referencestoarticlesorjournalswithtopicsthatarenotmuchdifferent.Suchassearchingontheinternet,books, as well as from thesis, final assignments and journals belonging to seniors. Therefore, if the final assignment raised by a student has also been appointed by a senior with the same thing, make the reference not as a basic reference for research but more as a cheat material by playing with words so they don't look the same. And for supervisors who do not have time to look for senior final assignments with similar titles to check one by one. Therefore,this makesstudentsuncriticalofthe topicsraised,so thatthewritingofthefinalprojectseemstojust makeanordinaryassignmentpaper.In this study, to measure the final project document of Padang State Polytechnic students, 4 methods of similarity processing were used. That is using the Rabin-Karp, Jaro-Winkler, Hybrid (Rabin-Karp and Jaro-Winkler Combination) andHybrid algorithms withtextmining normalization.Of thefour methodscomparedto which method is suitable for processing final project documents that have more than 10000 words and a relatively short processing time. By examining various aspects, it was found that the Rabin-Karp algorithm is suitable for this case with a shorter processing time and a higher percentage than the Jaro-Winkler algorithm. Therefore, the Jaro-Winkler algorithm is more suitable for systems to check for typo sentences, online essay exams, auto correct typo sentences or suggestions in the search column because the algorithm compares each character.